Developing effective marketing communication strategies for FMCG firms in rural India - Suchanti, Pooja (2006)
Occupational changes and the expansion of media have fuelled the rise of a new rural hinterland and a new rural consumer. Rural India, accounting for over 75% of Indias population offers a tremendous opportunity for generating volume-driven growth. FMCG majors have seen the potential of rural markets and have worked on their strategies to penetrate these areas.